Hubungan Penerapan Standard Sanitation Operational Procedure (SSOP) Terhadap Mutu Daging Ditinjau Dari Tingkat Cemaran Mikroba - Kuntoro, Bambang; Maheswari, Rarah RA; Nuraini, Henny (Jurnal Ilmiah Ilmu-Ilmu Peternakan, 2012)
Meat is animal origin food and serve as a source of animal protein for human nutrition. High demand for meat is not always followed by improvement of facilities and condition in slaughterhouses. This study was conduncted to examine the relationship between the implementation of the Standard Sanitation Operational Procedure (SSOP) at Slaughterhouse to the level of microbial contamination in meat. Random sampling was arranged  on a population of livestocks owned by five merchants at Pekanbaru City Slaughterhouse,  three heads respectively. Carcass parts analyzed microbially were Bicepfemoris (BF) and Longissimus dorsi lumbarum (LD). The variables  observed were the evaluation of the application of SSOP, establishment number and microbiological analysis (total plate count, E. coli, Coliform and Salmonella). The results showed that  SSOP evaluation from eighteen characteristics implemented was 54.65%,  and the assessment establishment number deviations indicate that there were 57 minor, 35 major, 14 serious and 8 critical (pre establishment number level). Below maximum implementation of SSOP, closely related to the high level of microbial contamination in  meat. Microbial analysis results (TPC, E.coli and Coliform) showed above the maximum limit set by the Indonesian National Standard (INS  3932:2008), while for Salmonella analysis was negative. In conclusion,  the application of SSOP in Pekanbaru City Slaughterhouse was not implemented well as shown by establishment number and  high level of microbiological contamination (TPC, E.coli and coliform).